Pain management in the neonatal piglet during routine management procedures. Part 2:Grading the quality of evidence and the strength of recommendations. (13th June 2014) - O'Connor, A.; Anthony, R.; Bergamasco, L.; Coetzee, J.; Gould, S.; Johnson, A. K.; Karriker, L. A.; Marchant-Forde, J. N.; Martineau, G. S.; McKean, J.; Millman, S. T.; Niekamp, S.; et al.
Abstract Piglets reared in swine production in the USA undergo painful procedures that include castration, tail docking, teeth clipping, and identification with ear notching or tagging. These procedures are usually performed without pain mitigation. The objective of this project was to develop recommendations for pain mitigation in 1- to 28-day-old piglets undergoing these procedures. The National Pork Board funded project to develop recommendations for pain mitigation in piglets. Recommendation development followed a defined multi-step process that included an evidence summary and estimates of the efficacies of interventions. The results of a systematic review of the interventions were reported in a companion paper. This manuscript describes the recommendation development process and the final recommendations. Recommendations were developed for three interventions (CO2/O2 general anesthesia, non-steroidal anti-inflammatory drugs (NSAIDs), and lidocaine) for use during castration. The ability to make strong recommendations was limited by low-quality evidence and strong certainty about variation in stakeholder values and preferences. The panel strongly recommended against the use of a CO2/O2 general anesthesia mixture, weakly recommended for the use of NSAIDs and weakly recommended against the use of lidocaine for pain mitigation during castration of 1- to 28-day-old piglets.